EDUCATIONAL AND PROFESSIONAL POTENTIAL OF MOSCOW YOUTH AND PROBLEMS OF ITS IMPLEMENTATION (based on the results of a sociological study) - A. L. Sazonova (Модернизация, инновация, развитие, 2015)
The article considers the educational and professional trends among theMoscowyouth, factors affecting on them, as well as challenges of realizing of their own potential in the field of professional activity.